3I index: A new method to examine the competitiveness of countries’ international publication productivity - Wu, Feng; Djurovic, Gordana (Malaysian Journal of Library and Information Science, 2018)
This study proposes a new method called the 3I index to examine the competitiveness of countries’ international publication productivity with indicators in three dimensions: International participation, International impact, and International leadership. Using the data (1996–2014) from the Scopus database in the communication field, we rank each country by its competitiveness score. The results reveal a polarized structure of competitiveness among all countries: The United States occupies the leading position with the highest score, Western European countries are in dominant positions with high scores, and marginalized countries (mostly in Asia, Africa, and Latin America) have lower levels of competitiveness. However, emerging countries, particularly Brazil, Russia, India, China, and South Africa (BRICS), recently have achieved great progress in international participations and impacts, that are expected to change the imbalance in international competitiveness in the near future. The regression analysis suggests that countries’ economic growth status (Gross Domestic Product) and human resources (total population) have significant impacts on the competitiveness of their international publication productivity. Finally, the authors suggest that both BRICS and developed countries should increase their governments’ supports to help third-world countries participate international academic cooperation.